Adjuvant ozone therapy in necrotizing soft tissue infection. Presentation of a case - Isidro Lamote Matos; Jorge Enrique Rodríguez León; Maydelin Pérez Reina; Niuvys Valera Rodríguez (Medisur)
Necrotizing soft tissue infections are characterized by extensive and progressive deterioration of surrounding tissues. This work continues the ozone therapy topic as a complementary and therapeutic technique in patients with this type of infections, as well as its approach in Primary Health Care. The case of a 73-year-old patient with a diagnosis of phlyctenular lymphangitis with a large area of necrosis in the right leg is presented. The area was debrided and systemic and topical antibiotics were administered until clinical stability was achieved. After the third week, it was necessary to repeat the debridement, with removal of slough and necrotic tissues. After the fourth week he was discharged, with follow-up and recommendations to the Basic Health Team, which included the combination of local ozone therapy and rectal insufflations. In week 26, elements of favorable evolution began to be observed: control of local signs of sepsis, granulation mainly at the edges and gradual disappearance of pain, among others. The described case confirms the therapeutic effectiveness of ozone therapy use as a complementary technique, specifically in the approach to necrotizing soft tissue infections.